Foundations of machine learning - Mohri, Mehryar; Rostamizadeh, Afshin; Talwalkar, Ameet (Cambridge The MIT Press, 2018)
This book is a general introduction to machine learning that can serve as a textbook for graduate students and a reference for researchers. It covers fundamental modern topics in machine learning while providing the theoretical basis and conceptual tools needed for the discussion and justification of algorithms. It also describes several key aspects of the application of these algorithms. The authors aim to present novel theoretical tools and concepts while giving concise proofs even for relatively advanced topics.
Keywords: Machine learning; Computer algorithms